Kurikulum Pendidikan Islam dalam Perspektif Hadits Tarbawi - Dinda Amanda Ainun Nuzul (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
The curriculum has two meanings, in a narrow sense curriculumis a number of subjects taken by students in an educational institution, and in a broad sense curriculum is "what persons experience in a setting" all experiences and learning culture created by an educational institution to build independence and achieve the desired educational goals. Meanwhile, the Islamic education curriculum is an educational curriculum that has a foundation based on Islam, namely the Qur'an and Hadith, which pays close attention to the personality conditions of humans or students such as physical aspects, intellectual aspects and spiritual aspects. Hadith as the second source of law after the Koran is the foundation in the preparation of the Islamic education curriculum. But indeed we will not find a special word in the Hadith such as manhaj al-dirasah as a word that denotes curriculum. So the curriculum in Tarbawi Hadith studies is in the form of a range of values, culture, character, principles, teachings that are spread out in the hadith treasures, which are examples of the application of the Koran by the Prophet Muhammad SAW